(untitled) (Revista de História Regional, 2023)
The 1890s marks the beginnings of journalism in Ponta Grossa, with traces of the existence of three journals installed in the city, entitled Campos Geraes, O Pirolita and O Precursor. These journals emerged in a period of reconfiguration of local, state and national society, with political transformations with the passage from the Brazilian Empire to the Republic, social transformations with the end of enslavement and the arrival of immigrants, and cultural transformations with the institution of republican discourses and the rise of the ideology of progress and social ordering. This investigation used an evidential paradigm, following the trail of signs, evidence and traces of sources about the beginnings of journalism in Ponta Grossa available in regional collections and in the Hemeroteca Digital Brasileira. The article aims to bring a reflection on the beginnings of journalism in Ponta Grossa, studying the signs of the existence of the press in the city, their founders, political and ideological content and the challenges of the foundation and survival of journalism in Ponta Grossa at the end of the 19th century. Keywords: History of journalism; Ideologies; Ponta Grossa.